Proposed new interior design scheme of Bell & Ross boutique outlet for FJ Benjamin (M) Sdn Bhd at Lot 224,225 and 226 The Gardens, Mid Valley City, Lingkaran Syed Putra, 59200 Kuala Lumpur. / Megat Abdul Zaim Megat Azizan - Megat Azizan, Megat Abdul Zaim (Faculty of Architecture, Planning and Surveying, 2011)
The final project of Interior Design for diploma is the expression of students in understanding on design process aspects of interior design that has been studied. In three years of studies, a student has gathered much knowledge and skills and should be put to practice and onto the drawing board. Not only that, as a final year, student should able to demonstrate in project research, case study, interviewing the clients, designing proposals, preparing drawing and to present the final outcome. The chosen product for this project is a boutique for Bell & Ross, a Swiss’s brand watch. The proposed site is situated at Lot 224, 225 and 226, The Gardens, Mid Valley City, Lingkaran Syed Putra, 59200 Kuala Lumpur. The idea of this project is to introduce this product to Malaysian and to fulfill the client mission which is to expand their business in Asia From the research arid observation conducted on the product and the site, all the information and details were gathered and was used as the guideline in preparing the design of this project. The objective; of this project is to design the first Bell & Ross boutique in Malaysia so that they can expand their business wider attract customers not only the foreign customers but also the local customers. This project also is to design a place for their own retail in Malaysia. The final design of this; retail would give the desired image projection that is needed to improve the interest of the luxury watch user in Malaysia especially.